О двух сущностях человека. „Задумчивый странник” Зинаиды Гиппиус - Okroj, Kinga (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is an attempt to describe the conception of androgyny in ZinaidaGippius’s work entitled Reflective wanderer. The main character of Reflective wandereris a modernistic philosopher, Vasily Rozanov. The aim of this article is to analyse the image of Rozanov and prove that he is an example of androgynous man being.